Hypopharyngeal squamous cell carcinoma: Three‐dimensional or Intensity‐modulated radiotherapy? A single institution's experience. (24th November 2015) - Katsoulakis, Evangelia; Riaz, Nadeem; Hu, Man; Morris, Luc; Sherman, Eric; McBride, Sean; Lee, Nancy
Abstract : Objectives/Hypothesis: Compare outcomes of hypopharyngeal carcinoma that received conventional radiotherapy versus intensity‐modulated radiotherapy (IMRT). Study Design: Retrospective single‐institution trial. Methods: Between April 1990 and May 2011, 100 patients with hypopharyngeal cancer underwent curative radiotherapy (RT) at our institution: 50 with IMRT and 50 with conventional RT. The median age was 63 years. There were 12 T1, 22 T2, 37 T3, and 28 T4 patients. The majority of patients (82%) had nodal disease: 54% N2 and 8% N3. The majority of patients (83%) received chemotherapy. Of the patients who received chemotherapy, 84% received a platinum‐based regimen. The median RT dose was 7, 000 cGy. The majority of patients (62%) had prophylactic percutaneous endoscopic gastrostomy tube placement. Toxicities were reviewed. Local control (LC), locoregional control (LRC), freedom from distant metastasis (FFM) rates, functional larynx preservation (LP), laryngectomy‐free survival (LFS), and overall‐survival (OS) curves were generated using the Kaplan‐Meier method. The log‐rank test was used to test prognostic variables. Results: With a median follow up of 48.4 months, the 3/5‐year LC, LRC, FFM, LP, LFS and OS rates were 74%/69%, 77%/74%, 70%/66%, 51%/29%, 49.6%/31.8%, and 49%/34%, respectively. The median OS was 2.9 years. The 3‐year LC rate for IMRT was 77% versus 81% for conventional RT ( P = .91); 3‐year LRC for IMRT was 85% versus 76% for conventional RT ( P = .32). There was no increased local failure with IMRT. There was no difference in the rate of stricture with IMRT (32%) versus conventional RT (25.3%) ( P = .86). Conclusions: IMRT achieved comparable LC and LRC rates to conventional RT. Level of Evidence: 4 Laryngoscope, 126:620–626, 2016